'The Worst Moment of My Life': Argentina, the 2002 World Cup, and the Global Public Sphere. Issue 2 (13th August 2021) - Richter, Daniel
Abstract: This study explores the political and social significance of Argentina national team at the 2002 World Cup in Asia against the global backdrop of Argentina's economic crisis in 2001–2002. The efforts of the national team players in seeking to emphasize their solidarity with the Argentine people through mass media before and after their ouster from the tournament took on global significance. The public statements of members of the Argentine national team are considered as local and global projections. The national team's lofty expectations and early exit from the tournament offers an important avenue of historical reinterpretation for understanding the Argentine crisis played out in a global context.